Organization of the Escherichia coli aerobic enzyme complexes of oxidative phosphorylation in dynamic domains within the cytoplasmic membrane. Issue 3 (12th April 2014) - Erhardt, Heiko; Dempwolff, Felix; Pfreundschuh, Moritz; Riehle, Marc; Schäfer, Caspar; Pohl, Thomas; Graumann, Peter; Friedrich, Thorsten
Abstract The Escherichia coli cytoplasmic membrane contains the enzyme complexes of oxidative phosphorylation (OXPHOS). Not much is known about their supramolecular organization and their dynamics within the membrane in this model organism. In mitochondria and other bacteria, it was demonstrated by nondenaturing electrophoretic methods and electron microscopy that the OXPHOS complexes are organized in so‐called supercomplexes, stable assemblies with a defined number of the individual enzyme complexes. To investigate the organization of the E. coli enzyme complexes of aerobic OXPHOS in vivo, we established fluorescent protein fusions of the NADH:ubiquinone oxidoreductase, the succinate:ubiquinone oxidoreductase, the cytochrome bd‐I, and the cytochrome bo3 terminal oxidases, and the FoF1 ATP‐synthase. The fusions were integrated in the chromosome to prevent artifacts caused by protein overproduction. Biochemical analysis revealed that all modified complexes were fully assembled, active, and stable. The distribution of the OXPHOS complexes in living cells was determined using total internal reflection fluorescence microscopy. The dynamics within the membrane were detected by fluorescence recovery after photobleaching. All aerobic OXPHOS complexes showed an uneven distribution in large mobile patches within the E. coli cytoplasmic membrane. It is discussed whether the individual OXPHOS complexes are organized as clustered individual complexes, here called "segrazones."